GAYA BAHASA DALAM WACANA IKLAN PRODUK KOSMETIK DI FACEBOOK - Damayanti, Rini (Universitas Wijaya Kusuma Surabaya, 2019)
This language about the style of language by focusing discourse cosmetic products in facebook advertising. In this research methods in a descriptive qualitative. The data obtained from facebook. The purpose of this research to described use of language. The result of this research described the language used in cosmetics in facebook advertising a product in the force in terms of language covering on climax, anticlimax and repetitions.